2013
DOI: 10.1097/id.0000000000000003
|View full text |Cite
|
Sign up to set email alerts
|

Photofunctionalization Enhances Bone-Implant Contact, Dynamics of Interfacial Osteogenesis, Marginal Bone Seal, and Removal Torque Value of Implants

Abstract: Photofunctionalization enhanced the morphology, quality, and behavior of periimplant osteogenesis, including the increased BIC, expedited robust interfacial bone deposition, and improved marginal bone seal and support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 30 publications
1
30
1
Order By: Relevance
“…All implants placed in tibias and femurs were unloaded. In detail, most authors reported significantly increased BIC [57,71,[73][74][75][76][77][78][79], push-in values [40,44,[80][81][82][83], bone volume [72,84], or bone mineral [85,86] were noted in all animal models studied for photofunctionalized groups disregarding implant surface modifications/topography. The differences were insignificant for both UV-treated and non-UV-treated reported in four animal studies [87][88][89][90].…”
Section: Resultsmentioning
confidence: 99%
“…All implants placed in tibias and femurs were unloaded. In detail, most authors reported significantly increased BIC [57,71,[73][74][75][76][77][78][79], push-in values [40,44,[80][81][82][83], bone volume [72,84], or bone mineral [85,86] were noted in all animal models studied for photofunctionalized groups disregarding implant surface modifications/topography. The differences were insignificant for both UV-treated and non-UV-treated reported in four animal studies [87][88][89][90].…”
Section: Resultsmentioning
confidence: 99%
“…22 Photofunctionalisation enhances osteogenesis around the implant, increases interfacial bone deposition on Ti, and improves the marginal bone seal and support. 23 It has been suggested that photofunctionalisation induces denser cortical bone formation and a stiffer bone connection compared with control implants. 22 …”
Section: Discussionmentioning
confidence: 99%
“…In terms of BIC assessment, photofunctionalization improved bone-to-implant contact in the initial healing period with statistically significant differences at 2 and 4 weeks of follow-up, regardless of the animal model used (Kim et al, 2016;Park et al, 2013;Pyo, Park, Moon, Lee, & Ogawa, 2013;Sawase et al, 2007;Takahashi et al, 2016;Yamauchi et al, 2017). In contrast, 12 weeks after implant placement, there were no differences between and among the groups (Kim et al, 2016;Park et al, 2013).…”
Section: F I G U R Ementioning
confidence: 88%